La teologia di Papa Francesco per l’oggi e il futuro della Chiesa (II Parte) Papa Francesco e la Teologia delle origini - Sinopoli, Concetta (Alpha omega, 2014)
The characteristics of Catholic theology, studied in the first part of the article, allow for an investigation of the innovative theological traits of Pope Francis’s Magisterium. His explicative and affective theology, with touches on the Heart of Christ and Mercy, has shown new paths of the Teacher among his own. Themes such as the call to evangelical coherence, the call to conversion so as to announce Christ, the Truth of Man, communion, renewal ad intra and ad extra of the Church and renewal of the life of believers for true transformation, poverty and suffering in our world, all seem to refound theological, pastoral and spiritual reflection, in the sensum fidelium and in the scientia Dei, for contemporary humanity. The call for a concrete response, for collaboration and for mutual membership of the People and their Pastors in unity, gives value to the personal commitment and responsibility of each person for the common human destiny, which is the way of holiness and announcement, both for today and for the future of the Church.